Reading mine closure through Tłı̨chǫ self-determination - John B Zoe; Rebecca Jane Hall; Tee Wern Lim (Journal of Political Ecology)
In Northern Canada, the Tłı̨chǫ have experienced a long history of settler-imposed mining. The history of the mines is written into Tłı̨chǫ place names that hold the knowledge of ecological harm and repair, the community re-purposing of mining equipment and refuse. This history and the broader context of past and present colonial dispossession of Indigenous peoples has shaped the contemporary engagement of Tłı̨chǫ with diamond mines, the largest extractive operations in the region; the Northwest Territories of Canada. The northern diamond industry is contracting, and all territorial diamond mines will likely cease production by 2035. In this article, John B. Zoe, knowledge holder and Chair of Dedats'eetsaa: Tłı̨chǫ Research and Training Institute, shares the Tłı̨chǫ experience with the diamond mines, and, as the diamond industry contracts, community experiences with and concerns surrounding forthcoming closure. Writing with collaborators and settler scholars, Rebecca Hall and Tee Wern Lim, Zoe contextualizes the community-industry agreements shaping the diamond mine closures in the long history of settler-Indigenous treaty making. While tracing the substantive gains the Tłı̨chǫ have made in their influence over mining operations on their territory, the article points to the problems that persist, as Tłı̨chǫ continue to struggle for self-determination over their lands, and extractive operations on these lands. Indeed, greater community employment and contracting with the diamond mines means that their closure will bring with it an economic rupture not experienced with past mine closure. Ultimately, Zoe asks, what is Tłı̨chǫ closure? What is an Indigenous-led approach to closure, and how might this approach make way for a future grounded in Indigenous relations to land? In response, he argues that the activities of mine closure, and subsequent economic development, must be grounded in Tłı̨chǫ land, language, culture and way of life.